Constructing the ‘liberal’ Muslim other: ethnic politics, competition, and polarisation in Malaysia - Saleem, Saleena (Religion, state & society, 2021)
This contribution extends the sectarianisation thesis to analyse the construction of the ‘liberal’ Muslim other in Malaysian politics. It argues that political competition, rather than religion, motivated elite Malay state actors to otherise their political rivals as ‘liberal’. Elite state actors leveraged key periods of sociopolitical uncertainty between 1998 and 2020 to reaffirm dominant ethno-religious narratives and construct the meaning of ‘liberal’ as anti-Islam to retain political power. They framed ‘liberal’ Malays as a threat by associating them with non-Malay ethnic minorities and, by extension, with secular values. The contribution builds its argument with an analysis of competing ideas over three time periods, each constituting cumulative stages in the sectarianisation of the ‘liberal’ Muslim other: the 1998 pro-democracy Reformasi movement; religious freedom challenges in the 2000s; and the mounting electoral challenges to the Barisan Nasional government since the 2008 general elections. The analysis demonstrates that the construction of ‘liberal’ sectarian difference occurred despite the absence of a pre-existing ‘liberal’ Muslim identity available for manipulation. The contribution emphasises that sectarianisation can develop in different forms and over cumulative stages that are contingent on local-level complexities and political competition.